Systematic review of suicidal behaviour and related issues of wellbeing in the veterinary profession - Platt, BJ (2010)
Population-based studies of suicide prevalence have identified certain occupational groups to be at particularly high risk of suicide. There is recent evidence that rate of suicide may also be significantly elevated in the veterinary profession. However, relatively little is known about the contributory factors that may explain this phenomenon. The present study is the first systematic review of the research literature on the prevalence of, and factors associated with, suicidal behaviour in the veterinary profession. An extensive search strategy was performed in order to identify studies that presented data on these issues. Studies were categorised into two main groups: those that presented epidemiological data from observational studies of suicide prevalence and those that were survey-based studies of suicidal behaviour and associated issues of wellbeing in the veterinary profession. In total, 89 papers were included in the final review. Nineteen studies of suicide prevalence were identified and 11 of these provided data on the relative risk of suicide in the veterinary profession. All but one of these studies found suicide to be significantly elevated in the veterinary profession. Interpretation of studies of highest quality found that the proportion of suicide in the veterinary profession was at least four times that of the general population. Data from 70 survey-based papers identified the prevalence of various aspects of suicidal behaviour in veterinary populations and the psychiatric, occupational and psychological risk factors that may help explain the reasons for the elevated rate of suicide in the veterinary profession. Knowledge of suicidal behaviour and wellbeing in the veterinary profession is still very much in its early stages. The limitations of research studies reviewed have been identified and suggestions made about the direction of future research. Suggestions for methods of preventing suicide in this high-risk group are also made, based on the current research reviewed, and existing strategies in other groups at high risk of suicide.